2015
DOI: 10.4236/jbm.2015.311009
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Indices in Patients with Acute Coronary Syndrome

Abstract: The platelet indices Mean Platelet Volume (MPV), Platelet Distribution Width (PDW) and Plateletcrit (PCT) provided by automated hematology analysis are rarely used in clinical practice. Platelets play a central role in the pathogenesis of acute coronary syndromes (ACS) and high MPV has been associated to more reactive platelets and regarded as an independent risk factor for myocardial infarction. In this study, platelet indices were evaluated in 39 patients with ACS presenting two altered biochemical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
3
3
0
Order By: Relevance
“…This study also failed to find any significant difference in PCT among three ACS groups. The previous studies conducted by Al-Obeidi et al, Pipliwal et al, and Costa et al also found similar 24,29,30 results with this recent study.…”
Section: Resultssupporting
confidence: 90%
“…This study also failed to find any significant difference in PCT among three ACS groups. The previous studies conducted by Al-Obeidi et al, Pipliwal et al, and Costa et al also found similar 24,29,30 results with this recent study.…”
Section: Resultssupporting
confidence: 90%
“…According to previous studies, increased prothrombotic activity can be ascertained by carefully analysing PVI and the presence of large platelets reflected as high MPV are associated with a greater aggregation potential causing thrombus formation, which is a risk factor for AMI, UA and stroke. [1,5,6] Our results corroborate with previous findings that underlines the essential role of platelets in AMI and UA, suggesting that MPV and PDW are related to platelet anisocytosis including macroplatelets that may contribute as independent haematological marker to cardiovascular risk. [7] Generalized platelet activation is the hallmark of an acute coronary event.…”
Section: Discussionsupporting
confidence: 82%
“…But it was significantly higher in AMI/UA as compared to controls. [1,4,6] We also found significantly increased PDW in AMI/UA. Using logistic regression analysis of PDW quartiles, we found value of more than 12.65 fL having sensitivity and specificity of 80% and 77.1% respectively.…”
Section: Discussionsupporting
confidence: 53%
“…As the results of this research, a research conducted by Pervin et al, 4 showed that there were significant differences in PDW value between ACS patients, and normals (p=0.001) with the mean PDW value of 16.23 ± 2.56 for the ACS patients, and 11.89 ± 1.42 for the control ones. 4 Costa et al, 13 also argued that there were significant differences in PDW value between ACS patients, and controls (p=0.01). 13 In also, the results of the Mann-Whitney post hoc test found that there was no significant difference in PDW value between STEMI group, and NSTEMI group (p=0.320), between STEMI group, and UAP group (p=0.980), as well as between NSTEMI group, and UAP group (p=0.435).…”
Section: Methodsmentioning
confidence: 95%